Comparison of low dose magnesium sulphate regime with standard Pritchard regime in severe preeclampsia and eclampsia: a tertiary centre experience - Gaur, Indu; Kumar, Kanishka (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: We tried to see if omitting the intravenous (IV) loading dose of magnesium sulphate (MgSo4) would result in similar outcome in comparison to the standard loading dose (intravenous+intramuscular) in eclampsia in preventing convulsions. Methods: Patients were randomized into 2 groups. In group A (modified Pritchard regimen), IV loading dose of MgSo4 was omitted (only IM loading dose was given) and maintenance dose was given for 12 hours. In group B, standard Pritchard regimen was followed, both IV and IM given as loading dose and maintenance dose was given for 24 hours. Our aim was to see if modified Pritchard regimen was as effective as the standard Pritchard regimen. Results: There was no difference in age, parity, gestational age at presentation, mode of child birth between both regimens. After 1 hour of loading dose, in both pre-eclampsia (PE) and eclampsia patients, in both groups A and B, therapeutic range of MgSo4 was reached with added benefit of less propensity of toxicity in group A (as IV dose was omitted). Out of 64 women with eclampsia, recurrent convulsions were seen in 6 women (20.68%) of group A and 11 women (31.4%) of group B (p=0.333). None of the women of severe PE had convulsion after loading dose of MgSO4 in either of the two groups. Conclusions: We conclude that efficacy of reduced loading dose regimen (omitting IV loading dose) and 12 hour maintenance dose of MgSo4 is similar to standard Pritchard regimen (which employs full loading dose and 24 hour maintenance dose) in both prophylaxis of convulsion in severe preeclampsia and controlling convulsion and preventing recurrent convulsion in eclampsia with the obvious lower propensity for MgSo4 toxicity.